LncRNA CASC9 interacts with CPSF3 to regulate TGF-β signaling in colorectal cancer - Luo, Kaili (J Exp Clin Cancer Res, 2019)
BACKGROUND: Colorectal cancer (CRC) is the third most frequent cancer and the second leading cause of cancer-related death worldwide. Increasing evidence indicates that the deregulation of long noncoding RNAs (lncRNAs) contributes to tumor initiation and progression; however, little is known about the biological role of cancer susceptibility candidate 9 (CASC9) in CRC. METHODS: Novel lncRNAs potentially involved in CRC tumorigenesis were identified from datasets downloaded from The Cancer LncRNome Atlas and The Atlas of Noncoding RNAs in Cancer. The CRC cell lines HCT-116, HCT-116 p53(−/−), SW620, SW480, HT-29, LoVo, LS-174T, and RKO were used. Colony-formation, MTS, cell-cycle, apoptosis, and in-vivo tumorigenesis assays were used to determine the role of CASC9 in CRC cell growth in vitro and in vivo. Potential interaction between CASC9 and cleavage and polyadenylation specificity factor subunit 3 (CPSF3) was evaluated using RNA immunoprecipitation and RNA-protein pull-down assays. RNA-sequencing was performed to analyze gene expression following CASC9 knockdown. RT-qPCR, western blotting, and mRNA decay assays were performed to study the mechanisms involved. RESULTS: CASC9 was frequently upregulated in CRC, which was correlated with advanced TNM stage, and higher CASC9 levels were associated with poor patient outcomes. Knockdown of CASC9 inhibited growth and promoted apoptosis in CRC cells, whereas ectopic CASC9 expression promoted cell growth in vitro and in vivo. We demonstrated that CPSF3 is a CASC9-interacting protein, and knockdown of CPSF3 mimicked the effects of CASC9 knockdown in CRC cells. Furthermore, we found that CASC9 exerts its oncogenic activity by modulating TGFβ2 mRNA stability and upregulating the levels of TGFβ2 and TERT, resulting in an increase in phosphorylated SMAD3 and activation of TGF-β signaling, and enhanced TERT complex function in CRC cells. Finally, CPSF3 was significantly upregulated in CRC tissues as compared with adjacent or non-adjacent normal colon tissues, and CASC9, CPSF3, and TGFβ2 levels in human CRC tissues were positively correlated. CONCLUSIONS: CASC9 is a promising prognostic predictor for patients with CRC and the CASC9-CPSF3-TGFβ2 axis is a potential therapeutic target for CRC treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1263-3) contains supplementary material, which is available to authorized users.